Implementation of The Merdeka Campus Policy At Dharmawangsa University - Novita Sari; Tien Rafida; Candra Wijaya (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to uncover and analyze (1) the process of redesigning the Merdeka Learning-Independence Campus curriculum implemented at Dharmawangsa University. (2) Independent Learning-Independent Campus Program held at Dharmawangsa University. (3) Implementation of the Free Learning-Free Campus Policy implemented at Dharmawangsa University. (4) Supporting and inhibiting factors for the implementation of the Free Learning-Free Campus policy implemented at Dharmawangsa University. This type of research used qualitative research. Data collection techniques include: observation, interviews and documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results of this study: (1) the process of redesigning the curriculum based on the background with the existence of policies, the involvement of the work team in the implementation of MBKM, the mechanism by conducting collaboration or partnerships, the results of the redesigning of the MBKM curriculum with the existence of the MBKM guidebook. (2) The programs to be implemented, namely eight programs according to those offered by the Ministry of Education and Culture, (3) Implementation of the Undhar MBKM program must meet the terms and conditions so that they can take part in the MBKM program and the programs that have been implemented are 8 programs, of the eight programs there are programs that superior, (4) Study of supporting factors in the Undhar MBKM program, namely the existence of rewards, certificates, and studies of inhibiting factors, namely the lack of student interest in participating in MBKM due to work, ignorance of information on MBKM program selection, lack of student ability to use the MBKM program application.